The estimation of the effect of expertise on postural control in shooting task with sample entropy - Juras, G.; Zajac, R.; Bril, G.; Slomka, K.; Sobota, G.; Baci, B. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
We aimed to determine the interdependence between functional and dynamic stability of young players. Eight elite biathlon experts, 15 moderate experienced subjects and 15 novices took part in the experiment. The postural sway and complexity of CoP signal and its decomposed trajectories were measured using force plate. Results indicate that highly trained group of elite biathlon athletes was characterized by decreased values describing body sway and increased value of Sample Entropy during quiet stance. However, that situation was changed during maintaining a shooting position and during aiming at the target. These results lead to the conclusion that Sample Entropy could be used to estimate the attentional involvement in postural control according to skill development in sport performance.